Can screening for degenerative cervical myelopathy (SCREEN-DCM) be effectively undertaken based on signs, symptoms and known risk factors? Rationale and research protocol for a prospective, multicentre, observational study - Benjamin Davies; Mark Kotter; Granit Molliqaj; Enrico Tessitore; Karl Schaller; Teresa Somma; Aria Nouri; Renato Gondar; Joseph S Cheng; Paolo Cappabianca; Alexandre Lavé; Gianpaolo Jannelli; et al. (BMJ Open)
Introduction Degenerative cervical myelopathy (DCM) is the most common cause of spinal cord impairment. Unfortunately, the condition remains poorly recognised and underdiagnosed. To better identify patients, screening tests that target individuals at high risk would be helpful. One group in particular known to have a high prevalence of DCM consists of patients with lumbar degenerative disease (LDD), with the combined presentation referred to as tandem stenosis. Given that LDD is one of the most common presentations in neurosurgical practice and primary care, it is the objective of the proposed study to administer a screening test to these patients as well as those with risk factors or symptoms which raise the suspicion of underlying DCM.Methods and analysis A screening test based on clinical signs/symptoms and known risk factors of DCM was designed. Screening will be performed in neurosurgical consultations for patients with LDD or those with any suspicion of myelopathy. Points are attributed based on the presence of signs/symptoms of DCM (eg, Hoffmann sign, hyper-reflexia) and for comorbidities that predispose or are frequently associated with cervical myelopathy (eg, rheumatoid arthritis, carpal tunnel syndrome). Patients with ≥3 points undergo cervical MRI examination. Patients with positive MRIs will be consulted and receive assessment via modified Japanese Orthopedic Association and Neck Disability Index scores, and subsequent clinical management will be based on practice guidelines. An exploratory multivariate analysis of the effectiveness and efficiency of this proposed screening test will be evaluated after positively screening 50 patients for DCM.Ethics and dissemination This study has received research ethics approval from the Swiss Association of Research Ethics Committees (ID: 2020-02785). The results of this study will be disseminated in a journal targeting physicians commonly encountering patients with LDD.